PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. INDOMAKMUR SAWIT BERJAYA RAMBAH HILIR KABUPATEN ROKAN HULU - SUDARJAT, ASEP (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This study aims to determine employee training, employee productivity levels, and to determine the effect of training on the productivity of employees at PT. Indomakmur Sawit Berjaya Rambah Hilir Rokan Hulu. By sampling consists of a number of selected members of the population that is 42 employees who have been trained. The data analysis technique used is quantitative analysis. Data analysis methods used are validity, reliability, simple regression analysis, correlation analysis, coefficient of determination, t-test by using SPSS 19.0 for windows. And the results of this study stated that The training has been adopted already said to be good company, because TCR value of the training acquired by 71.2%. As for variable employee productivity gained 81.6% TCR value is said to be very good. And training effect on employee productivity. Based on the analysis of the data shows that simultaneously, Training effect on employee productivity, with thitung > t table is equal to 2,354> 1,683. The relationship between training and employee productivity obtained value of R square = 0.122. Therefore it can be concluded that the training variables significantly influence the productivity of employees at PT. Indomakmur Sawit Berjaya Rambah Hilir Kabupaten Rokan Hulu.